TANTANGAN OVERSUPPLY : ANALISIS KINERJA KEUANGAN, STRATEGI MANAJERIAL, DAN DAMPAK KEBIJAKAN PERUSAHAAN SEMEN BERBASIS DI SUMATERA SELATAN TAHUN 2023-2024 - Bahar, Amirul; Rizki, Tabah; Renta, Muhammad Prans Panca (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
The increasingly intense competition in the national cement industry, coupled with the challenges of oversupply in Indonesia’s cement sector, fuel price volatility, and global economic uncertainty, has placed PT Semen Baturaja Tbk—one of the state-owned cement producers operating in South Sumatra—in a critical position. The year 2024 marks a crucial period for the company as it faces industrial pressure due to national cement oversupply, rising production costs, and tight market competition. This study employs a descriptive quantitative approach by analyzing the company’s published annual financial statements for 2023 and 2024. The analysis results show that despite the oversupply in the national cement market, PT Semen Baturaja managed to increase its net profit while maintaining a healthy liquidity level. Cost-efficiency strategies and market penetration in the Sumatra region remain the primary focus of management. Overall, PT Semen Baturaja demonstrates moderate financial resilience amid external pressures. Adaptive managerial strategies and internally driven efficiency policies are key to sustaining business continuity. However, strategic innovation and market diversification are needed to enhance future competitiveness and financial performance.